The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1111/imb.12562
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA miR‐252 targets mbt to control the developmental growth of Drosophila

Abstract: Developmental growth is an intricate process involving the coordinated regulation of the expression of various genes, and microRNAs (miRNAs) play crucial roles in diverse processes throughout animal development. The ecdysone‐responsive miRNA, miR‐252, is normally upregulated during the pupal and adult stages of Drosophila development. Here, we found that overexpression of miR‐252 in the larval fat body decreased total tissue mass through a reduction in both cell size and cell number, causing a concomitant decr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 50 publications
0
19
0
Order By: Relevance
“…Pxy-miR-252 belonged to the miR-252 family. It has been found that miR-252 could directly repress the mbt expression to control the developmental growth of Drosophila ( Lim et al, 2019 ) and was also involved in dengue virus replication in Aedes albopictus ( Yan et al, 2014 ). Pxy-miR-274 was classified into the miR-274 family.…”
Section: Discussionmentioning
confidence: 99%
“…Pxy-miR-252 belonged to the miR-252 family. It has been found that miR-252 could directly repress the mbt expression to control the developmental growth of Drosophila ( Lim et al, 2019 ) and was also involved in dengue virus replication in Aedes albopictus ( Yan et al, 2014 ). Pxy-miR-274 was classified into the miR-274 family.…”
Section: Discussionmentioning
confidence: 99%
“…To test the efficiency of RNAi lines for Vha knockdown, flies carrying either hs‐GAL4 only ( hs‐GAL4 /+) or both hs‐GAL4 and each of the experimental UAS‐RNAi transgenes ( hs > Vha‐RNAi ) were heat‐shocked at the wandering L3 stage at 37°C for 40 minutes and then cultured at 25°C for 36 hours prior to analysis. A flip‐out clonal assay was performed by crossing hsFLP; Actin > CD2 > GAL4 , UAS‐nlsGFP flies with the experimental UAS transgenic flies or w 1118 flies, as described previously 25 …”
Section: Methodsmentioning
confidence: 99%
“…Target sites for miRNA binding in the 3′‐UTR of the corresponding genes were assessed by a luciferase reporter assay as described previously 25 . Primer sets that were used to construct the luciferase reporters are listed in Table S4.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations